The Effectivity of Prenatal Massage Therapy in the Third Trimester of Pregnancy on Back Pain Complaints - Karmila Daud Bone Bolango; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Back pain is a common complaint among pregnant women, particularly during the third trimester, due to physiological changes such as increased body weight, shifting of the body’s center of gravity, and hormonal influences that loosen ligaments, as well as biomechanical changes in posture and gait. If not managed properly, back pain can negatively affect maternal comfort, mobility, and quality of life during pregnancy. One non-pharmacological method that has been shown to alleviate such discomfort is prenatal massage, which aims to reduce muscle tension, improve circulation, and promote relaxation. This study aims to determine the effect of prenatal massage on back pain in third-trimester pregnancy at PHC Bulango. A quantitative approach was applied using a pre-experimental one-group pretest–posttest design. A total of 30 pregnant women in their third trimester participated as respondents, selected based on inclusion criteria. Data were collected through observation and structured interviews using a standardized pain scale to measure back pain intensity before and after the intervention. Prenatal massage was administered following recommended maternal health protocols to ensure safety and comfort. Data analysis was performed using the paired t-test to compare mean pain scores before and after the intervention. The results showed a statistically significant reduction in pain levels, with a p-value of 0.000 (p < 0.05), indicating that prenatal massage had a meaningful effect in alleviating back pain among participants. The findings support the conclusion that prenatal massage is an effective, safe, and easily applicable non-pharmacological intervention for reducing back pain in third-trimester pregnant women. Based on these results, prenatal massage can be recommended as a complementary practice in antenatal care services to enhance maternal comfort and well-being during pregnancy, alongside other supportive health interventions.